2010
DOI: 10.1016/j.yhbeh.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of hormonal and metabolic rhythms during fasting in 7- to 9-day-old rabbits entrained by nursing during the night

Abstract: Rabbit does nurse their litter once every 24 h during the night. We hypothesized that corticosterone, ghrelin, leptin and metabolites like glucose, liver glycogen and free fatty acids could be affected in the pups by the time at which does nurse them. Therefore, we measured these parameters in pups nursed at 02:00 h (nighttime for the doe) to compare them with results from a previous study where does nursed at 10:00 h, during daytime. From postnatal day 7, pups were sacrificed either just before their schedule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 68 publications
5
50
0
Order By: Relevance
“…A similar pattern in neuronal activity has been observed with c-Fos immunohistochemistry in the rabbit pup (Nolasco et al, 2012) and in the adult rat (Caba et al, in press). In this last study, under a restricted feeding schedule, a parallel pattern of activation was found in the piriform cortex and bed nucleus of the accessory olfactory tract, which are main targets of OB.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…A similar pattern in neuronal activity has been observed with c-Fos immunohistochemistry in the rabbit pup (Nolasco et al, 2012) and in the adult rat (Caba et al, in press). In this last study, under a restricted feeding schedule, a parallel pattern of activation was found in the piriform cortex and bed nucleus of the accessory olfactory tract, which are main targets of OB.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, it was shown that the main OB of neonatal rabbits expresses circadian oscillations of both c-Fos and Per1 proteins, which were entrained by circadian nursing (Nolasco et al, 2012). This result shows a possible functional significance of OB oscillations, suggesting that olfactory signals during nursing might be the primary entraining cue.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Rabbit pups show clear locomotor anticipatory behavior and a significant increase of corticosterone before the arrival of the nursing mother (Caba et al, 2008;Jilge, 1995;Morgado et al, 2010a), which occurs with circadian periodicity (González-Mariscal et al, 2013;Jilge, 1995). Besides, the diffuse part of the dorsomedial nucleus (DMN; Caba et al, 2008) and parabrachial nucleus (PBN; Juárez et al, 2012) are entrained by the timing of feeding, but not the SCN (Caba et al, 2008), similar to rodents (Mistlberger, 2011).…”
Section: Introductionmentioning
confidence: 99%